2008
DOI: 10.1097/bpo.0b013e318164f8e7
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Clubfoot With the Ponseti Method

Abstract: Level II. Nonblinded randomized controlled prospective study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
38
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(39 citation statements)
references
References 16 publications
0
38
0
1
Order By: Relevance
“…Though Ponseti advocates the use of plaster for the cast material as it is easier to mold, there are reports on the successful use of fiberglass materials for achieving clubfoot correction [15,53]. Regardless of the casting material used, the casts are changed every 5 to 7 days [48].…”
Section: Ponseti Methodsmentioning
confidence: 99%
“…Though Ponseti advocates the use of plaster for the cast material as it is easier to mold, there are reports on the successful use of fiberglass materials for achieving clubfoot correction [15,53]. Regardless of the casting material used, the casts are changed every 5 to 7 days [48].…”
Section: Ponseti Methodsmentioning
confidence: 99%
“…31 This situation might be further exacerbated by difficulties with cast handling and removal. Interestingly, in the study by Pittner and colleagues, 30 there was no difference in parental satisfaction between the 2 casting groups. Further study using validated questionnaires is required to definitively answer the question relating psychological well-being to ease of cast removal and the relative importance of a parental preference in clubfoot casting material.…”
Section: Discussionmentioning
confidence: 96%
“…Since the commencement of the present study, Pittner and colleagues 30 have reported the results of the first randomized trial comparing POP to SRF. As in the present study, there was no significant difference in the mean number of casts required for Ponseti correction between the 2 groups (6.1 in the SRF group v. 5.2 in the POP group, p = 0.20).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1,2,3,4,5 Casting with plaster-of-Paris has been the historical standard for clubfoot immobilization since it was introduced by Guerin. 1,4,6 Traditionally, plaster-of-Paris has been long praised for its moldability and patient comfort for serial casting purposes. On the other hand, it can be heavy, takes a long time to dry completely, and requires soaking for several hours or a cast saw to remove it, risking skin injury.…”
Section: Introductionmentioning
confidence: 99%